STRATEGY FOR THE USE OF ARTIFICIAL INTELLIGENCE IN HUMAN RESOURCE MANAGEMENT IN THE PUBLIC SECTOR - Temelkovska, Ivana (KNOWLEDGE - International Journal, 2025)
In the third decade of the 21st century, the public sector in the era of the digital revolution and artificial intelligence is characterized by several specificities. The specificity of the public sector, in addition to other domains, is also reflected in the domain of human resource management. The purpose of this essay is to analyze the importance and specificities of human resource management in public administration. Such an approach to this matter assumes systematization and elaboration of the main challenges that public administration will have to face in the short and medium term in human resource management. In human resource management in public administration, several dimensions are imposed, of which the following stand out: a) the size of the administration in the public sector. b) the socio-economic aspects that direct the public administration and public authorities to adapt in accordance with the spirit of the new era. Indeed, today it is clear that the functioning and maintenance of public administration also requires significant budgetary resources. The obligation of every public administration in the era of digitalization and artificial intelligence is to adapt to the new conditions of strategic management. In order to bridge such a gap, the administration is obliged to understand the goals and technology of that process. This goal assumes the availability of certain funds and tools provided by public authorities, and to perceive the fact that it is part of a more global system. In this context, political support is important, which is often indifferent due to the absence of transferable, visible and tangible successes. Social networks have taught people to communicate, to exchange data despite different climates, reliefs, climates, borders or large geographical distances. There is a huge number of individuals from the public administration who own the Internet, are hooked on social networks and benefit from this technological invention in various domains. Although a large number of individuals from the public administration enjoy social networks, in their work content such a transformation is long overdue. The engagement of the public administration in this domain is determined by the strategic management of human resources. But previously, a certain political transformation is necessary in the direction of decentralizing innovation units, with an appropriate degree of freedom and own resources. It should be borne in mind that this process must be accelerated given that digital changes are very fast, and in such conditions a race between possibilities and reality is created. Only in this way will the trust and functionality of the state increase, which must stimulate the strategy of human resources management in the direction of improving digital capabilities.